Seismic Hazard Analysis with a Deterministic Approach in Boroujerd City - Yegane, Ali Ghiyas; Solgi, Ali; Uromeie, Ali; Maleki, Zahra; Nezafati, Nima (International Journal of Psychosocial Rehabilitation, 2020)
With the help of seismic techniques and event analysis (from the point of view of temporal and spatial distribution), the mechanical nature of fractures can be determined using the physical parameters of the seismic source. However, long-term seismology (study of prehistoric events) has not been considered in Iran due to its high costs, and due to the presence of historical information in the study area, the behavior of seismic springs can be studied to some extent. Due to advances in seismic knowledge, the seismicity of each zone can be divided into two periods before and after the 20th century BC. The events of the 20th century BC can also be divided into two half-periods of the initial apparatus before 1963 and half of the new apparatus after 1963. In this study, to perform seismic analysis of the region, the catalog of historical and instrumental earthquakes that occurred in the region was firstly collected. Then, according to the available sources (reports, scientific articles, seismotectonics maps, etc.), active faults, and seismic springs in the area were determined. Finally, the seismicity of the area was analyzed using seismic data and faults.